PELATIHAN KOMPUTER DESAIN CANVA BAGI ANAK REMAJA DI DESA MOJOSARI KEPANJEN MALANG - Setyorini Setyorini; Hutri Agustino; Syarif Hidayatullah; Ike Kusdyah Rachmawati (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
With the development of technology, inevitably the world of education will be required to be able to recognize technology, mingle with technology, and master technology. One of them is in the field of computer graphic design. To fulfill these needs, he provided Canva Design Computer training for teenagers in Mojosari Village, Kepanjen Malang. The purpose of this activity is to improve Computer Graphic Design skills using Canva which is simple and easy to learn. From the evaluation of community service activities that have been carried out, it is clear that this training can provide benefits, is targeted and effective in providing new knowledge in the field of Computer Graphic Design.